Zebrafish deficient for Muscleblind-like 2 exhibit features of myotonic dystrophy - Laura E. Machuca-Tzili; Sarah Buxton; Aaran Thorpe; Cathy M. Timson; Peter Wigmore; Pradeep K. Luther; J. David Brook (The Company of Biologists, 2011)
SUMMARY Myotonic dystrophy (DM; also known as dystrophia myotonica) is an autosomal dominant disorder that affects the heart, eyes, brain and endocrine system, but the predominant symptoms are neuromuscular, with progressive muscle weakness and wasting. DM presents in two forms, DM1 and DM2, both of which are caused by nucleotide repeat expansions: CTG in the DMPK gene for DM1 and CCTG in ZNF9 (CNBP) for DM2. Previous studies have shown that the mutant mRNAs containing the transcribed CUG or CCUG repeats are retained within the nuclei of cells from individuals with DM, where they bind and sequester the muscleblind-like proteins MBNL1, MBNL2 and MBNL3. It has been proposed that the sequestration of these proteins plays a key role in determining the classic features of DM. However, the functions of each of the three MBNL genes are not completely understood. We have generated a zebrafish knockdown model in which we demonstrate that a lack of mbnl2 function causes morphological abnormalities at the eye, heart, brain and muscle levels, supporting an essential role for mbnl2 during embryonic development. Major features of DM are replicated in our model, including muscle defects and splicing abnormalities. We found that the absence of mbnl2 causes disruption to the organization of myofibrils in skeletal and heart muscle of zebrafish embryos, and a reduction in the amount of both slow and fast muscle fibres. Notably, our findings included altered splicing patterns of two transcripts whose expression is also altered in DM patients: clcn1 and tnnt2. The studies described herein provide broader insight into the functions of MBNL2. They also lend support to the hypothesis that the sequestration of this protein is an important determinant in DM pathophysiology, and imply a direct role of MBNL2 in splicing regulation of specific transcripts, which, when altered, contributes to the DM phenotype.